2019
DOI: 10.1259/bjr.20180989
|View full text |Cite
|
Sign up to set email alerts
|

Extremity CT and ultrasound in the assessment of ankle injuries: occult fractures and ligament injuries

Abstract: Objective: To assess the rates of fractures and ligament injuries in patients with an acute ankle injury and a normal radiographic examination, and to consider the most appropriate examination protocol. Methods: Patients with an acute ankle injury who presented to the John Radcliffe Hospital Emergency Department with a normal radiographic examination were eligible for the study. They were invited to receive a cone beam CT and ultrasound examination at a local radiology department within 5 days of their ankle i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
0
25
0
5
Order By: Relevance
“…Because occult fractures account for 2%-36% in a conventional X-ray on account of overlapping structures, under-mineralized ossification centres and non-perpendicular X-ray beam to the fracture line [35]. Several studies have demonstrated that multiplanar capabilities of ultrasound might make it superior to radiography in the detection of occult fractures that the X-ray has missed [37,38]. Banal et al found that in cases of normal radiographs, US is indicated in the diagnosis of metatarsal bone stress fractures with a sensitivity of 0.83 and a specificity of 0.76 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Because occult fractures account for 2%-36% in a conventional X-ray on account of overlapping structures, under-mineralized ossification centres and non-perpendicular X-ray beam to the fracture line [35]. Several studies have demonstrated that multiplanar capabilities of ultrasound might make it superior to radiography in the detection of occult fractures that the X-ray has missed [37,38]. Banal et al found that in cases of normal radiographs, US is indicated in the diagnosis of metatarsal bone stress fractures with a sensitivity of 0.83 and a specificity of 0.76 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although direct X-ray is accepted as the primary imaging modality in skeletal trauma, MDCT has become an important adjunct imaging method especially in the trauma of regions with a complex anatomy [12,13]. CT is not only used to better understand the fracture anatomy and make a surgical plan for both adult and child patients but also to investigate the occult pelvis, extremity, and vertebral fractures for which direct X-ray showed negative results [4,14,15]. It is often difficult to obtain a conventional radiographic series in trauma cases, and full-adaptation of patients to necessary positions cannot be achieved owing to pain.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior tibiofibular and talofibular ligament can also be injured and assessed by ultrasound. Deltoid ligament injury is also common (in 50% of lateral ligament injuries) [32]. Dynamic assessment of all the ankle ligaments is possible with ultrasound including the posterior ligaments best seen using a small footprint.…”
Section: Key Pointsmentioning
confidence: 99%